Find the value of \[\int {\dfrac{1}{{3 + 2\sin x + \cos x}}dx} \] .
Answer
Verified
459.9k+ views
Hint: Here we will write all the terms in the form of \[\tan x\] by using the below-mentioned formulas:
\[\sin x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] , \[\cos x = \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] and \[\tan x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 - {{\tan }^2}\dfrac{x}{2}}}\] .
Complete step-by-step solution:
Step 1: We will replace the terms \[\sin x\] and \[\cos x\] by substituting the values of them in the form of \[\tan x\] as shown below:
\[I = \int {\dfrac{1}{{3 + 2\left( {\dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right) + \left( {\dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right)}}dx} \]
By opening the brackets and multiplying \[2\]inside the term \[\left( {\dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right)\] , we get:
\[ \Rightarrow I = \int {\dfrac{1}{{\dfrac{{4\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}} + \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}} + 3}}dx} \] ……………………….. (1)
Step 2: By taking \[1 + {\tan ^2}\dfrac{x}{2}\] common from the denominator and adding the numerator terms in the above expression (1), we get:
\[ \Rightarrow I = \int {\dfrac{1}{{\dfrac{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}{{1 + {{\tan }^2}\dfrac{x}{2}}}}}dx} \]
By bringing \[1 + {\tan ^2}\dfrac{x}{2}\] into the numerator position, we get:
\[ \Rightarrow I = \int {\dfrac{{1 + {{\tan }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}dx} \] ………….. (2)
As we know that \[1 + {\tan ^2}\dfrac{x}{2} = {\sec ^2}\dfrac{x}{2}\] , so by replacing it in the above expression (2), we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}dx} \]
By opening the brackets in the denominator of the above expression we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3 + 3{{\tan }^2}\dfrac{x}{2} + 1 - {{\tan }^2}\dfrac{x}{2}}}dx} \]
By doing simple addition and subtraction in the denominator part of the above expression we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 2{{\tan }^2}\dfrac{x}{2} + 4}}dx} \] …………………… (3)
Step 3: Now, we will assume that \[\tan \dfrac{x}{2} = t\] and differentiating it w.r.t \[t\] , we get:
\[ \Rightarrow {\sec ^2}\left( {\dfrac{x}{2}} \right) \times \dfrac{1}{2}dx = dt\]
We can write the above expression as below by bringing \[2\] into the RHS side:
\[ \Rightarrow {\sec ^2}\left( {\dfrac{x}{2}} \right)dx = 2dt\]
By substituting these values in the expression (3), we get:
\[ \Rightarrow I = \int {\dfrac{{2dt}}{{4t + 2{\operatorname{t} ^2} + 4}}} \] \[\left( {\because \tan \dfrac{x}{2} = t,{{\sec }^2}\dfrac{x}{2}dx = 2dt} \right)\]
By dividing the RHS side with \[2\], we get:
\[ \Rightarrow I = \int {\dfrac{{dt}}{{2t + {\operatorname{t} ^2} + 2}}} \]
By writing the term \[2t + {\operatorname{t} ^2} + 2 = {\left( {t + 1} \right)^2} + {\left( 1 \right)^2}\]in the RHS side of the expression \[I = \int {\dfrac{{dt}}{{2t + {\operatorname{t} ^2} + 2}}} \] , we get:
\[ \Rightarrow I = \int {\dfrac{{dt}}{{{{\left( {t + 1} \right)}^2} + {{\left( 1 \right)}^2}}}} \] …………………. (4)
Step 4: As we know that \[\dfrac{1}{{{x^2} + {a^2}}}dx = \dfrac{1}{a}{\tan ^{ - 1}}\dfrac{x}{a} + {\text{c}}\] , where \[{\text{c}}\] is an arbitrary constant. Comparing the above expression (4) with this formula, we get:
\[ \Rightarrow I = \dfrac{1}{1}{\tan ^{ - 1}}\dfrac{{\left( {t + 1} \right)}}{1} + {\text{c}}\]
By substituting the value of \[t = \tan \dfrac{x}{2}\] , in the above expression we get:
\[ \Rightarrow I = {\tan ^{ - 1}}\left( {\tan \dfrac{x}{2} + 1} \right) + {\text{c}}\]
$ \therefore$ The value of \[\int {\dfrac{1}{{3 + 2\sin x + \cos x}}dx} = {\tan ^{ - 1}}\left( {\tan \dfrac{x}{2} + 1} \right) + {\text{c}}\]
Note: In solving these types of question students should remember some basic formulas as given below:
\[\sin x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] , \[\cos x = \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] and \[\tan x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 - {{\tan }^2}\dfrac{x}{2}}}\] , these are known as tangent half-angle formulas.
\[\dfrac{1}{{{x^2} + {a^2}}}dx = \dfrac{1}{a}{\tan ^{ - 1}}\dfrac{x}{a} + {\text{c}}\] , proof of which is showing below:
Suppose we need to evaluate the integral \[\dfrac{1}{{{x^2} + {a^2}}}dx\] for \[a \ne 0\]. So, by multiplying and dividing the expression with \[{a^2}\] , we get:
\[ \Rightarrow \int {\dfrac{1}{{{x^2} + {a^2}}}dx = \int {\dfrac{1}{{1 + \dfrac{{{x^2}}}{{{a^2}}}}}\dfrac{{dx}}{{{a^2}}}} } \]
Now by writing the terms \[\dfrac{x}{a} = u\] and differentiating it, we get:
\[ \Rightarrow \dfrac{{dx}}{a} = du\]
By substituting this value in the above expression \[\int {\dfrac{1}{{{x^2} + {a^2}}}dx = \int {\dfrac{1}{{1 + \dfrac{{{x^2}}}{{{a^2}}}}}\dfrac{{dx}}{{{a^2}}}} } \] , we get:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}\int {\dfrac{{du}}{{1 + {u^2}}}} } \]
We can write the above expression as below:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}{{\tan }^{ - 1}}u + {\text{c}}} \] , where \[{\text{c}}\] is an arbitrary constant.
By substituting the value of \[\dfrac{x}{a} = u\] in the above expression, we get:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}{{\tan }^{ - 1}}\dfrac{x}{a} + {\text{c}}} \]
\[\sin x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] , \[\cos x = \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] and \[\tan x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 - {{\tan }^2}\dfrac{x}{2}}}\] .
Complete step-by-step solution:
Step 1: We will replace the terms \[\sin x\] and \[\cos x\] by substituting the values of them in the form of \[\tan x\] as shown below:
\[I = \int {\dfrac{1}{{3 + 2\left( {\dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right) + \left( {\dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right)}}dx} \]
By opening the brackets and multiplying \[2\]inside the term \[\left( {\dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}} \right)\] , we get:
\[ \Rightarrow I = \int {\dfrac{1}{{\dfrac{{4\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}} + \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}} + 3}}dx} \] ……………………….. (1)
Step 2: By taking \[1 + {\tan ^2}\dfrac{x}{2}\] common from the denominator and adding the numerator terms in the above expression (1), we get:
\[ \Rightarrow I = \int {\dfrac{1}{{\dfrac{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}{{1 + {{\tan }^2}\dfrac{x}{2}}}}}dx} \]
By bringing \[1 + {\tan ^2}\dfrac{x}{2}\] into the numerator position, we get:
\[ \Rightarrow I = \int {\dfrac{{1 + {{\tan }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}dx} \] ………….. (2)
As we know that \[1 + {\tan ^2}\dfrac{x}{2} = {\sec ^2}\dfrac{x}{2}\] , so by replacing it in the above expression (2), we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3\left( {1 + {{\tan }^2}\dfrac{x}{2}} \right) + \left( {1 - {{\tan }^2}\dfrac{x}{2}} \right)}}dx} \]
By opening the brackets in the denominator of the above expression we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 3 + 3{{\tan }^2}\dfrac{x}{2} + 1 - {{\tan }^2}\dfrac{x}{2}}}dx} \]
By doing simple addition and subtraction in the denominator part of the above expression we get:
\[ \Rightarrow I = \int {\dfrac{{{{\sec }^2}\dfrac{x}{2}}}{{4\tan \dfrac{x}{2} + 2{{\tan }^2}\dfrac{x}{2} + 4}}dx} \] …………………… (3)
Step 3: Now, we will assume that \[\tan \dfrac{x}{2} = t\] and differentiating it w.r.t \[t\] , we get:
\[ \Rightarrow {\sec ^2}\left( {\dfrac{x}{2}} \right) \times \dfrac{1}{2}dx = dt\]
We can write the above expression as below by bringing \[2\] into the RHS side:
\[ \Rightarrow {\sec ^2}\left( {\dfrac{x}{2}} \right)dx = 2dt\]
By substituting these values in the expression (3), we get:
\[ \Rightarrow I = \int {\dfrac{{2dt}}{{4t + 2{\operatorname{t} ^2} + 4}}} \] \[\left( {\because \tan \dfrac{x}{2} = t,{{\sec }^2}\dfrac{x}{2}dx = 2dt} \right)\]
By dividing the RHS side with \[2\], we get:
\[ \Rightarrow I = \int {\dfrac{{dt}}{{2t + {\operatorname{t} ^2} + 2}}} \]
By writing the term \[2t + {\operatorname{t} ^2} + 2 = {\left( {t + 1} \right)^2} + {\left( 1 \right)^2}\]in the RHS side of the expression \[I = \int {\dfrac{{dt}}{{2t + {\operatorname{t} ^2} + 2}}} \] , we get:
\[ \Rightarrow I = \int {\dfrac{{dt}}{{{{\left( {t + 1} \right)}^2} + {{\left( 1 \right)}^2}}}} \] …………………. (4)
Step 4: As we know that \[\dfrac{1}{{{x^2} + {a^2}}}dx = \dfrac{1}{a}{\tan ^{ - 1}}\dfrac{x}{a} + {\text{c}}\] , where \[{\text{c}}\] is an arbitrary constant. Comparing the above expression (4) with this formula, we get:
\[ \Rightarrow I = \dfrac{1}{1}{\tan ^{ - 1}}\dfrac{{\left( {t + 1} \right)}}{1} + {\text{c}}\]
By substituting the value of \[t = \tan \dfrac{x}{2}\] , in the above expression we get:
\[ \Rightarrow I = {\tan ^{ - 1}}\left( {\tan \dfrac{x}{2} + 1} \right) + {\text{c}}\]
$ \therefore$ The value of \[\int {\dfrac{1}{{3 + 2\sin x + \cos x}}dx} = {\tan ^{ - 1}}\left( {\tan \dfrac{x}{2} + 1} \right) + {\text{c}}\]
Note: In solving these types of question students should remember some basic formulas as given below:
\[\sin x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] , \[\cos x = \dfrac{{1 - {{\tan }^2}\dfrac{x}{2}}}{{1 + {{\tan }^2}\dfrac{x}{2}}}\] and \[\tan x = \dfrac{{2\tan \dfrac{x}{2}}}{{1 - {{\tan }^2}\dfrac{x}{2}}}\] , these are known as tangent half-angle formulas.
\[\dfrac{1}{{{x^2} + {a^2}}}dx = \dfrac{1}{a}{\tan ^{ - 1}}\dfrac{x}{a} + {\text{c}}\] , proof of which is showing below:
Suppose we need to evaluate the integral \[\dfrac{1}{{{x^2} + {a^2}}}dx\] for \[a \ne 0\]. So, by multiplying and dividing the expression with \[{a^2}\] , we get:
\[ \Rightarrow \int {\dfrac{1}{{{x^2} + {a^2}}}dx = \int {\dfrac{1}{{1 + \dfrac{{{x^2}}}{{{a^2}}}}}\dfrac{{dx}}{{{a^2}}}} } \]
Now by writing the terms \[\dfrac{x}{a} = u\] and differentiating it, we get:
\[ \Rightarrow \dfrac{{dx}}{a} = du\]
By substituting this value in the above expression \[\int {\dfrac{1}{{{x^2} + {a^2}}}dx = \int {\dfrac{1}{{1 + \dfrac{{{x^2}}}{{{a^2}}}}}\dfrac{{dx}}{{{a^2}}}} } \] , we get:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}\int {\dfrac{{du}}{{1 + {u^2}}}} } \]
We can write the above expression as below:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}{{\tan }^{ - 1}}u + {\text{c}}} \] , where \[{\text{c}}\] is an arbitrary constant.
By substituting the value of \[\dfrac{x}{a} = u\] in the above expression, we get:
\[ \Rightarrow \int {\dfrac{{dx}}{{{x^2} + {a^2}}} = \dfrac{1}{a}{{\tan }^{ - 1}}\dfrac{x}{a} + {\text{c}}} \]
Recently Updated Pages
Master Class 12 Social Science: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Master Class 12 Chemistry: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Trending doubts
Explain sex determination in humans with the help of class 12 biology CBSE
Give 10 examples of unisexual and bisexual flowers
Distinguish between asexual and sexual reproduction class 12 biology CBSE
How do you convert from joules to electron volts class 12 physics CBSE
Derive mirror equation State any three experimental class 12 physics CBSE
Differentiate between internal fertilization and external class 12 biology CBSE